PENGETAHUAN DAN SIKAP IBU TENTANG PENCEGAHAN DAN PENGENDALIAN INFEKSI NIFAS DI BELLA BORI DAN BELLA PUNRANGA KABUPATEN GOWA - Nadyah Haruna (Alami Journal (Alauddin Islamic Medical) Journal, 2017)
One  of  the  main  cause  of  maternal  mortality  is  postpartum infection which is the second number of  maternal  mortality in the world while in Indonesia it became the third after eclampsia and hemorrhage. Due to this condition this study want to  find  the overview of knowledgde and  attitude of women about the prevention and restraint of postpartum  infection in two villages Bella Bori and Bella Punranga  from 7 September to 13 December 2016. This study used descriptive method, primary data collected from 50 preganancy and post partum woman determined by purposive sampling in this two villages.The research showed that respondents who have a good knowledge about the prevention and restraint of postpartum infection were 18 respondens (36%) and the respondents who have lack of knowledge are 31 respondens (64%). Meanwhile in terms of attitude, 33 respondents (66%) who have positive attitude about the prevention and restraint of postpartum  infection and 17 respondents (34%) who have negative attitude.It is expected for each expactant to look for information more through read, follow the counselling, or discuss with health care providers in order to be able to apply the knowledge about the prevention and restraint of postpartum infection.